PROSEDUR PENETAPAN NOTA PEMBETULAN (NOTUL) DI KANTOR PELAYANAN UTAMA BEA DAN CUKAI TIPE A TANJUNG PRIOK JAKARTA - Jiwa Pribadi Agustino; Endro Andayani; Christovorus Anggoro Bani Kasapto (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
Cost in is the tax of the country depand from rules constitution for the things that come in to pabean area. From there the subyek of this final duty is How The Prosedure of Confirmatiom Correcting Note (NOTUL) at the Office of First Service Bea and Cukai type A Tanjung Priuk Jakarta. . Achivement from making this materi is to know the Prosedure of Confirmation Correcting Note  (NOTUL) at the Office of First Service Bea Cukai  Type A Tanjung Priuk Jakarta. The writer using some of the method collecting data with looking for dates from the countries that connacting import. The observation method that to do on this final duty from the study of the closing observation, collecting data method and dooing interview with the subyek. The Conclusion is Based on the Procedure of Stipulation of Notice in the Office of Main Customs and Excise Type A Tanjung Priok Jakarta in the period of 2017 is in accordance with the Law Number 17 of 2006 on the amendment to Law Number 10 Year 1995 About Customs.